Thromboembolic event index after total knee arthroplasty with the use of tranexamic acid: an integrative review (Research, Society and Development, 2022)
Total knee arthroplasty (TKA) is a surgical procedure that consists of replacing the weight-bearing surfaces of the affected joint with a prosthesis, aiming at relieving pain and correcting deformities. Due to the inherent risk of venous thromboembolism, drugs are used for its prophylaxis. This integrative literature review aimed to analyze the complications involved in the use of tranexamic acid in patients undergoing total knee arthroplasty (TKA), specifically the thromboembolic events that occurred. Studies were selected from PubMed, SciELO, Medline and Thieme electronic databases. Eleven randomized clinical trials were included. The total number of patients included in the studies was 1.299 who underwent TKA. In total, seven thromboembolic events were recorded, thus occurring in 0.5% of the cases analyzed. Thus, the safety of the use of tranexamic acid is proven, so that 99.5% of the patients did not present thromboembolic events, with the index relative to positive cases being practically irrelevant. Thus, the concluion is that the drug is safe and effective to be used in this surgical procedure, in order to minimize bleeding, rarely resulting in thromboembolic events.